2014
DOI: 10.1111/1462-2920.12601
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the uniqueness of Mucoromycotina cell walls by combining biochemical and phylogenomic approaches

Abstract: Most fungi from the Mucoromycotina lineage occur in ecosystems as saprobes, although some species are phytopathogens or may induce human mycosis. Mucoromycotina represent early diverging models that are most valuable for understanding fungal evolution. Here we reveal the uniqueness of the cell wall structure of the Mucoromycotina Rhizopus oryzae and Phycomyces blakesleeanus compared with the better characterized cell wall of the ascomycete Neurospora crassa. We have analysed the corresponding polysaccharide bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 66 publications
8
65
1
Order By: Relevance
“…sized that S. marcescens utilizes secreted chitinases to specifically target and kill zygomycete molds, because they contain unusually high levels of chitin (in the form of chitosan) in their cell walls (12). Surprisingly, we found that an S. marcescens triple-deletion mutant (⌬chiA ⌬chiB ⌬chiC) with no detectable secreted chitinase activity retained wild-type fungal killing abilities.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…sized that S. marcescens utilizes secreted chitinases to specifically target and kill zygomycete molds, because they contain unusually high levels of chitin (in the form of chitosan) in their cell walls (12). Surprisingly, we found that an S. marcescens triple-deletion mutant (⌬chiA ⌬chiB ⌬chiC) with no detectable secreted chitinase activity retained wild-type fungal killing abilities.…”
Section: Discussionmentioning
confidence: 82%
“…To measure the rate of bacterial spreading over fungal mycelia, fresh spores of R. oryzae 3465 were spread over an SOC plate at a concentration of 2.5 ϫ 10 4 spores/cm 2 , allowed to germinate for 12 h at 37°C, and then inoculated at the center of the plate by pipetting 5 l of bacterial suspension grown at 30°C in SOC to exponential phase (OD ϭ 0.5) on the agar surface. After incubation at 30°C, the plates were sampled by the insertion of a 96-pin metal replicator (of which 66 pins fit into the plate) into the agar and replication onto fresh SOC plates at 4,8,12, and 24 h postinoculation. Replicated plates were incubated for 24 h at 37°C, when bacterial colonies were clearly visible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fungal cell walls, there is a common fibrillar core composed of branched beta-(1,3)-glucan to which chitin and other polysaccharides are covalently bound. Chitin accounts for 1-2% of the cell wall mass in yeasts and up to 30% in molds [9, 10]. Elongation of the chitin polymer is catalyzed by a highly conserved enzyme called chitin synthase, CHS (UDP-N-acetyl-D-glucosamine: chitin 4-beta-N-acetylglucosaminyl-transferase; EC 2.4.1.16).…”
Section: Introductionmentioning
confidence: 99%
“…However, the activity of L1B against yeasts and A. niger was similar to that of NaD1. The observation that the enhancement in antifungal activity varied widely between fungal strains points to the potential involvement of the fungal cell wall, which varies between fungal species (33), and/or to differences in the ability of the fungi to respond to cell wall, osmotic, or oxidative stress (14,21). Variations in cell wall composition have been proposed as an explanation for the different effects that the defensin MtDef4 displays against Neurospora crassa and F. graminearum (34).…”
Section: Discussionmentioning
confidence: 99%